Phenotypic and Genotypic Determination of Biofilm Formation in Shiga Toxin-Producing Escherichia coli - Cáceres, María Emilia (2022)
Shiga toxin-producing Escherichia coli (STEC) O157:H7 is the most prevalent serotype associated with severe diseases worldwide. Biofilms by STEC O157:H7 constitute a high risk to public health and the food industry since they allow cross-contamination of surfaces and the consequent transmission to humans. This study aimed to detect the presence of adhesins genotypically and determine the ability to form biofilm and the curli expression in a collection of 30 O157:H7 strains from healthy cattle and human cases. The efa1, iha, fimCD, ehaA, lpfA1-3, and lpfA2-2 genes were detected in all strains; cah was frequently detected in strains isolated from humans (16/20), and agn43 was the least prevalent gene (3/30). All strains could form a biofilm, although those isolated from cattle were the most biofilm-formers. The curli-negative phenotype was the most prevalent phenotype observed at 37 °C and room temperature. The association between curli production and biofilm formation could not be determined, but the highest proportion of curli-positive strains at room temperature were strong biofilm-formers. These results highlight the possibility of the persistence of STEC O157:H7 in environmental conditions and food processing facilities, increasing the risk of contamination or infection.